2021
DOI: 10.1007/s11676-021-01388-8
|View full text |Cite
|
Sign up to set email alerts
|

Mastering the scientific peer review process: tips for young authors from a young senior editor

Abstract: Are you a student at a higher institution or an early-career researcher who is striving to understand and master the peer review process so to increase the odds of getting a paper published in the Journal of Forestry Research or another reputable, peer-reviewed, scientific journal? In this paper, a young, senior editor provides a handbook of the peer review process based on his decadal experience in scientific publishing. He covers major information you need to know during the entire process, from selecting jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 84 publications
1
10
0
Order By: Relevance
“…Even though the temporal perspective on course module activity and assignment submission (cluster 2) did not show differences between the male and female students, there were temporal differences in terms of the online learning behavior activities of clusters 1 and 3 (viewing achievement reports and the list of peers; forum interaction; see Figures 4 and 6). This is basically consistent with the findings in one prior study in China by Authors (2021). Moreover, this study went one step further than Authors (2021) and indicated that as the learning process progressed, females were more active than males, particularly for the activities involving viewed achievement and peers and forum interaction.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Even though the temporal perspective on course module activity and assignment submission (cluster 2) did not show differences between the male and female students, there were temporal differences in terms of the online learning behavior activities of clusters 1 and 3 (viewing achievement reports and the list of peers; forum interaction; see Figures 4 and 6). This is basically consistent with the findings in one prior study in China by Authors (2021). Moreover, this study went one step further than Authors (2021) and indicated that as the learning process progressed, females were more active than males, particularly for the activities involving viewed achievement and peers and forum interaction.…”
Section: Discussionsupporting
confidence: 91%
“…Zhai et al (2018) found that male students favor procedure feedback and female students prefer conclusive assessments in the context of online self-regulated learning. Authors (2021) found a gendered-related difference in Chinese students' transitional patterns in online learning behaviors.…”
Section: Gender and Online Learningmentioning
confidence: 89%
See 1 more Smart Citation
“…As explained in my previous paper (Agathokleous 2022), aretê is the ethical/moral excellence or supremacy (Yiaslas 2019). Keep this in mind while serving as a reviewer.…”
Section: Pursuit Aretêmentioning
confidence: 98%
“…In a previous paper, I have analyzed the peer-review process for beginner authors (Agathokleous 2022). If you have published your first article in the Journal of Forestry Research or Project funding:The author acknowledges support from The Startup Foundation for Introducing Talent of Nanjing University of Information Science &Technology (NUIST), Nanjing, China (Grant No.…”
Section: Why Should You Agree To Review a Paper?mentioning
confidence: 99%